Gambaran Format dan Kelengkapan Pengisian Sertifikat Kematian di Rumah Sakit : Sebuah Tinjauan Pustaka - Marwin, Fikri Alhafizd; Susanti, Rika; Fortuna, Fory; Windasari, Noverika; Rustam, Rony; Hasmiwati, Hasmiwati (Universitas Malahayati, 2024)
ABSTRACT Medical Certificate Cause of Death (MCCD) or death certificate is a letter made by the hospital and filled out by the doctor in charge to explain that someone has died. The standard format and instructions for filling out death certificates in Indonesia are issued by the Research and Development Agency of the Ministry of Health, Republic of Indonesia. In practice, several hospitals in Indonesia produce death certificates that do not comply with the standard format and do not follow the instructions for filling out the information issued by the Research and Development Agency of the Ministry of Health, Republic of Indonesia, so that death certificates are often filled out incompletely. This literature review aims to determine the suitability of the format and completeness of filling out a death certificate as well as the factors causing discrepancies and incomplete filling. This research takes the form of a literature review using provider databases, such as Google Scholar and nationally accredited journal sites with the keywords